Application of high-sensitivity flow cytometry in combination with low-voltage scanning electron microscopy for characterization of nanosized objects during platelet concentrate storage. (17th February 2020) - Fedorov, Anton; Kondratov, Kirill; Kishenko, Vasilii; Mikhailovskii, Vladimir; Kudryavtsev, Igor; Belyakova, Margarita; Sidorkevich, Sergey; Vavilova, Tatyana; Kostareva, Anna; Sirotkina, Olga; Golovkin, Alexey
Abstract: Platelet concentrates are used in clinic for therapy and prophylaxis of conditions associated with platelet deficiency or malfunction. The characteristics of platelet concentrates gradually change during pretransfusion storage, affecting their clinical effectiveness and the risk of adverse transfusion reactions. The presence of platelet-derived membrane vesicles is an important characteristic of platelet concentrates. Due to their functionality, changes in the number and molecular compositions of platelet-derived vesicles have major effects on the clinical properties of platelet preparations. The existence of different subpopulations of membrane vesicles requires analytical methods capable of providing information at the individual vesicle level. Such methods include flow cytometry and electron microscopy. However, conventional flow cytometry has certain limitations, since the diameters of many platelet-derived membrane vesicles are smaller than its detection limit. The use of classical scanning electron microscopy is also limited due to the requirement for coating with a layer of conductive material, which impedes the detection of small extracellular vesicles. Here, a combination of high-sensitivity flow cytometry and low-voltage scanning electron microscopy was used to increase sensitivity and resolution in the detection of nanosized objects present in platelet concentrates during storage. Apheresis platelet concentrates from eight healthy adult donors were investigated on days 2 and 7 of storage. Fractions of nanosized objects were obtained by differential centrifugation. Fluorophore-conjugated antibodies were used to detect marker-positive vesicles derived from platelets (CD41), red blood cells (CD235a), leukocytes (CD45), and endothelial cells (VEGFR2). Near-spherical objects with diameters ranging from 25 to 700 nm were observed by low-voltage scanning electron microscopy in platelet concentrates and its fractions. On day 7 of storage, objects with diameters of less than 100 nm were attached to and clustered near the terminal ends of pseudopod-like projections. High-sensitivity flow cytometry showed that during storage numbers of CD41(pos) vesicles elevated more than fivefold and numbers of marker-negative nanosized objects, which did not carry any of the investigated cell type-specific markers elevated more than twofold. Major changes in both CD41(pos) vesicles and marker-negative nanosized objects abundances were observed for objects with diameters around 100 nm bead equivalents. Overall, these results emphasized the importance of application of high-sensitivity methods for monitoring the characteristics of cell-derived nanosized objects during platelet concentrate storage.